37 Del. Laws 771 (1931) - (:unkn) unknown (My University, 1931)
Ch. 225, § 1: Prohibited the carry of a gun while training dogs in a closed game season. Violators fined not less than nor more than one hundred dollars with costs of prosecution, and shall be committed to the County jail for thirty days unless the fine and costs are paid sooner.
Keywords: CARRY